Peripheral immunity patterns, imaging features, and clinical outcomes in patients with gait impairment and ventriculomegaly on brain MRI - Espinoza-Vinces, Christian; Aviles-Olmos, Iciar; Núñez-Córdoba, Jorge M.; Jiménez-Vázquez, Marcos; Calvo-Imirizaldu, Marta; Montoya-Murillo, Genoveva; Martí-Andrés, Gloria; Arbizu, Javier; Luquin, María-Rosario (Frontiers in Aging Neuroscience, 2025)
IntroductionVentricular enlargement is a common finding on brain MRI in patients with gait impairment, particularly in those with idiopathic normal pressure hydrocephalus (iNPH). However, iNPH shares several clinical and radiological features with neurodegenerative diseases, which complicates accurate diagnosis. This study aimed to explore the associations between peripheral immune markers, imaging biomarkers, and final diagnosis in patients with gait disturbance and ventriculomegaly.MethodsWe retrospectively analyzed 55 patients with gait impairment and ventriculomegaly, and 40 age-comparable healthy controls. Clinical assessments included the iNPH Grading Scale (iNPHGS) and cognitive tests. The neutrophil-to-lymphocyte ratio (NLR) was calculated as a peripheral immune marker. Imaging biomarkers included Evans’ index (EI), callosal angle (CA), and disproportionately enlarged subarachnoid space hydrocephalus (DESH) score. Additional cerebrospinal fluid biomarkers and [18F]-fluorodopa PET/CT were used when clinically indicated. Patients were classified into two groups at the 5-year follow-up based on current clinical diagnostic criteria, integrating longitudinal clinical evaluation and ancillary investigations. The first group consisted of 35 patients (64%) with a neurodegenerative disorder (ND group), of whom 24 (69%) met criteria for progressive supranuclear palsy, 8 (23%) for Alzheimer’s disease, 2 (6%) for Lewy body dementia, and 1 (3%) for Parkinson’s disease. The remaining 20 patients (36%) fulfilled criteria for probable iNPH and were classified into the iNPH group.ResultsND patients had significantly higher NLR (M = 2.4, SD = 0.5) than iNPH patients (M = 1.9, SD = 0.4) and controls (M = 1.6, SD = 0.2; p < 0.001). NLR distinguished ND from iNPH with an AUC of 0.79 (80% sensitivity, 70% specificity at a cutoff of 2.0). CA demonstrated strong discrimination (95% sensitivity, 86% specificity). Compared to iNPH, ND had higher iNPHGS scores, greater DESH, and lower CA. Baseline NLR correlated with iNPHGS in ND patients (rs = 0.48, p = 0.004) but not in iNPH. NLR predicted tap test response differently; higher NLR was linked to non-response in ND, and lower NLR associated with improvement in iNPH.ConclusionNLR may serve as a promising peripheral biomarker to differentiate ND from iNPH in patients with gait impairment and ventriculomegaly. Integrating immune, clinical, and imaging markers could improve diagnostic accuracy and guide appropriate therapeutic strategies.